2011
DOI: 10.1038/nn.2907
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval-specific endocytosis of GluA2-AMPARs underlies adaptive reconsolidation of contextual fear

Abstract: Aversive associative memories formed by the association between a neutral conditioned stimulus (CS+) and an aversive unconditioned stimulus (US+) are progressively made permanent by a process of consolidation 1 . However upon retrieval, intervention by amnestic agents [2][3][4][5][6][7] , either prior to or immediately after retrieval, results in disruption of the previously consolidated fear memory. This suggests that a consolidated memory returns to a transient destabilized state shortly after reactivation n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
200
3
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(223 citation statements)
references
References 50 publications
(129 reference statements)
17
200
3
3
Order By: Relevance
“…Further, some studies have shown similar effects to those of Monfils et al (2009) using contextual fear preparations in mice (Rao-Ruiz et al 2011) while others show findings like ours in contextual paradigms (Ishii et al 2012). Although important to study, it is unlikely that the discrepant findings in the literature are simply due to procedural differences, such as the type of fear conditioning (cued or contextual), the postsession delay (immediate or 10 min), or differences in species.…”
Section: Discussionsupporting
confidence: 69%
“…Further, some studies have shown similar effects to those of Monfils et al (2009) using contextual fear preparations in mice (Rao-Ruiz et al 2011) while others show findings like ours in contextual paradigms (Ishii et al 2012). Although important to study, it is unlikely that the discrepant findings in the literature are simply due to procedural differences, such as the type of fear conditioning (cued or contextual), the postsession delay (immediate or 10 min), or differences in species.…”
Section: Discussionsupporting
confidence: 69%
“…The dorsal half of the hippocampus was dissected from fresh brains and stored at − 80°C (Rao-Ruiz et al, 2011). For the mPFC, brains were removed, rapidly frozen, and the area was dissected freehand from~1 mm coronal sections in a cryostat.…”
Section: Immunoblottingmentioning
confidence: 99%
“…Contextual FC was performed as described previously (Rao-Ruiz et al, 2011), with small modifications. In short, conditioning and testing was performed in a Plexiglas chamber with a stainless steel grid floor (Ugo Basil).…”
Section: Contextual Fear Conditioning (Fc)mentioning
confidence: 99%
“…Recently, it has been shown in mice (10,11), rats (12), and humans (13)(14)(15)(16)) that precisely timing behavioral extinction to coincide with memory reconsolidation can persistently inhibit the return of defensive reactions (but see refs. 17-19 for a discussion of boundary conditions).…”
mentioning
confidence: 99%